Genetic contribution to postpartum haemorrhage in Swedish population: cohort study of 466 686 births - Oberg, Anna Sara (BMJ Publishing Group Ltd., 2014)
Objective To investigate the familial clustering of postpartum haemorrhage in the Swedish population, and to quantify the relative contributions of genetic and environmental effects. Design Register based cohort study. Setting Swedish population (multi-generation and medical birth registers). Main outcome measure Postpartum haemorrhage, defined as >1000 mL estimated blood loss. Participants The first two live births to individuals in Sweden in 1997-2009 contributed to clusters representing intact couples (n=366 350 births), mothers with separate partners (n=53 292), fathers with separate partners (n=47 054), sister pairs (n=97 228), brother pairs (n=91 168), and mixed sibling pairs (n=177 944). Methods Familial clustering was quantified through cluster specific tetrachoric correlation coefficients, and the influence of potential sharing of known risk factors was evaluated with alternating logistic regression. Relative contributions of genetic and environmental effects to the variation in liability for postpartum haemorrhage were quantified with generalised linear mixed models. Results The overall prevalence of postpartum haemorrhage after vaginal deliveries in our sample was 4.6%. Among vaginal deliveries, 18% (95% confidence interval 9% to 26%) of the variation in postpartum haemorrhage liability was attributed to maternal genetic factors, 10% (1% to 19%) to unique maternal environment, and 11% (0% to 26%) to fetal genetic effects. Adjustment for known risk factors only partially explained estimates of familial clustering, suggesting that the observed shared genetic and environmental effects operate in part through pathways independent of known risk factors. There were similar patterns of familial clustering for both of the main subtypes examined (atony and retained placenta), though strongest for haemorrhage after retained placenta. Conclusions There is a maternal genetic predisposition to postpartum haemorrhage, but more than half of the total variation in liability is attributable to factors that are not shared in families.